(untitled) (Estudios de Historia de España, 2023)
The aim of this article is to study the male labour market in an inland city such as Segovia from 1860 to 1905, focusing on three representative professional groups: laborers, craftsmen and employees. For this and based on the systematic analysis of the municipal registers of 1860, 1881 and 1905, the registrations of industrial contribution, resistance societies, books of agreements of the City Council, Local Board of Health and contemporary local press, among others, the professional reality of these groups has been reconstructed, describing their main characteristics.